The Experiences of Homeless Youth When Using Strengths Profiling to Identify Their Character Strengths - Cooley, Sam J.; Quinton, Mary L.; Holland, Mark J. G.; Parry, Benjamin J.; Cumming, Jennifer (Frontiers in Psychology, 2019)
Individuals, particularly those considered ‘hard-to-reach’, often engage well with assessment tools that involve active dialog and the co-construction of knowledge. Strengths profiling is one such tool that enables a person-centered and autonomy supportive approach to the identification of character strengths. Strength profiling is an adaptation of performance profiling used in sport psychology, which has not yet been utilized in broader psychological research or applied practice. Supporting an individual by raising awareness of their personal character strengths is an effective and growing mechanism for achieving psychological well-being. Strengths profiling involves several stages of exploring, defining, and assessing character strengths, leading to the identification of signature strengths and goals for future development. Informed by personal construct theory, the present study explored the experiences of homeless young people living in sheltered accommodation (N = 116), when using strengths profiling at the start and end of a 10-week, strengths-based intervention. Mixed-method data was obtained from the strengths profiles, questionnaires measuring resilience, self-worth, and well-being, and diary entries. Findings revealed a rich array of character strength terminology and individual meanings. Participants found strengths profiling to be highly engaging, particularly due to their active role in strength identification, which prompted interesting and meaningful reflections on character strengths that were pertinent to them. Participants felt their signature strengths were vital protective factors within their lives and strengths profiles were correlated with resilience, self-worth, and well-being. Character strengths and resilience were also significantly and meaningfully improved pre/post intervention, providing support for the use of strengths profiling as a tool for monitoring change in character strength perceptions. Overall, this study demonstrates the utility and versatility of strengths profiling as a new method in the discipline of positive psychology and strengths-based research and applied practice.